Pulsed HDX Illuminates the Aggregation Kinetics of Alpha-Synuclein, the Causative Agent for Parkinson’s Disease - Illes-Toth, Eva (ACS Chem Neurosci, 2018)
Alpha-synuclein (aS) forms toxic intermediates ranging from small oligomers and protofibrils to large amyloid fibrils. Understanding the time course of aS fibril formation and the role played by its regions is critical for therapeutic intervention. Here, we used pulsed hydrogen-deuterium-exchange and mass spectrometry (HDX-MS) for the first time to probe kinetic intermediates of the full aS aggregation in vitro, achieving kinetic snapshots containing spatially resolved protein information about critical stages. Monitoring the resultant mass shifts show distinct binomial abundances for two main exchange profiles, one that represents a fast-exchanging, solvent-accessible species and another with a more protected nature. We show using a series of proteolytic peptides from the full protein that self-association is most pronounced in the NAC region and less so for either termini. The N-terminus, however, shows a minor protected population at mid- and late times, whereas the C-terminus shows predominantly unimodal HDX, indicating that these regions are devoid of any large conformational rearrangements. Focusing on the hydrophobic core, we confirmed and modeled the different isotopic distributions and calculated their relative fractions to discern their individual contributions. The data fitting reports respective t(1/2) values, which are nearly identical and do not depend on location. We followed the aggregation by complementary transmission electron microscopy to observe the morphology of aggregates and circular dichroism to assess changes in secondary structure. Our results provide a detailed picture of aS aggregation in vitro, and demonstrate that HDX-MS offers unique spatially resolved, co-existing kinetic intermediates in solution. This new platform is suitable for testing promising inhibitors of aS aggregation.